Ethnobotanical Studies in Nagarhaveli Forests-some Interesting Native Drugs - Bennet, S. S. R. (Indian Forester, 1978)
Nagarbaveli is a small enclave located between Gujarat and Maharashtra. The majority of the population are tribals. For the treatment of diseases these people consult their tribal herbalists who give them natural plant products as drugs. Some drugs are said to be efficacious. Therefore, this area has good scope for ethnobotanical studies. The plants with additional medicinal uses are as under. The data was collected from the tribals. Acacia ferruginea, Bridelia retusa, calycopteris floribunda, Carissa carandas, Cryptolepis huchanani, Cylista scariosa, Dalbergia volubilis, Derris scandens, Flemingia lineata, Helicteres inora, Heterophragma quadriloculare, Melia composita, Randia spinosa, Ventilago calyculuta, woodfordia fruticosa and Wrightia tinctoria.